Youth Appreciation of The Existence of Historical Buildings (Vredeburg Fort) - Muhammad Hasan Al Bashri; Emmelia Tricia Herliana (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2024)
Yogyakarta is a city that has a diverse history and cultural heritage both physically and non-physically. Physically in the form of buildings - historical heritage buildings such as the Vredeburg Fort building which is one of the relics of VOC colonialism in the city of Yogyakarta since 1765. Now its existence has changed its function to become a historical heritage fort and its presence as a historical heritage building now greatly affects the sense of concern in the current era, especially the younger generation of the current era. As a result, the awareness of knowing and appreciating historical buildings is low due to the advancement of civilisation. The purpose of this research is to explore the perceptions of young people that lead to appreciation of Fort Vredeburg in the current era. The research method applied by conducting observations, data collection and questionnaire interviews. The result of this research is to reveal the form of appreciation from young people's perception towards Fort Vredeburg today.